ҚАРАҚАЛПАҚ ПОЭЗИЯСЫНДА БӘНТ (ХХ әсирдиң 30-жылларындағы қарақалпак поэзиясы мысалында) - Мамбетов, И. (FAN va JAMIYAT, 2019)
The article deals with the types of Karakalpak poetic strophe in the thirties of the twentieth century. The types of the strophe are a couplet, a tercet, and a mukhammas were analyzed on the examples of folklore and literary artistic works, and conclusions are drawn accordingly on the Karakalpak versification of the thirties of the twentiteh century.